2009
DOI: 10.1007/s10549-008-0271-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel doxorubicin-mitomycin C co-encapsulated nanoparticle formulation exhibits anti-cancer synergy in multidrug resistant human breast cancer cells

Abstract: Anthracycline-containing treatment regimens are currently the most widely employed regimens for the management of breast cancer. These drug combinations are often designed based on non-cross resistance and minimal overlapping toxicity rather than drug synergism. Moreover, aggressive doses are normally used in chemotherapy to achieve a greater therapeutic benefit at the cost of more acute and long-term toxic effects. To increase chemotherapeutic efficacy while decreasing toxic effects, rational design of drug s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 32 publications
6
99
0
Order By: Relevance
“…To overcome this 30 problem several delivery strategies have been developed such as solid lipid nanoparticles and nanoliposomal 31 delivery systems, for example Doxil ® (Natarajan et al, 2014). Ion-exchange microspheres and, in particular, drug-eluting beads, have become the system of choice for drug delivery (Liu et al, 2001;Shuhendler et al, 2010). For 33 over a decade transarterial chemoembolisation using drug eluting beads (DEBs) has been a treatment option for 34 primary and secondary liver cancers.…”
mentioning
confidence: 99%
“…To overcome this 30 problem several delivery strategies have been developed such as solid lipid nanoparticles and nanoliposomal 31 delivery systems, for example Doxil ® (Natarajan et al, 2014). Ion-exchange microspheres and, in particular, drug-eluting beads, have become the system of choice for drug delivery (Liu et al, 2001;Shuhendler et al, 2010). For 33 over a decade transarterial chemoembolisation using drug eluting beads (DEBs) has been a treatment option for 34 primary and secondary liver cancers.…”
mentioning
confidence: 99%
“…[1,3] Since then, various PLN formulations have been developed to encapsulate a single anticancer drug, [4] or co-encapsulate a drug with a chemosensitizer, [1,3] a drug with a P-glycoprotein (P-gp) inhibitor, [5] or dual anticancer drugs of synergy. [6] PLN formulations have also been developed to deliver biologics for gene therapy and immunotherapy, including siRNA [7] or siRNA with an anticancer drug. [8] PLN formulations have been shown to circumvent efflux transporter-mediated multidrug resistance (MDR) in cancer cells [1,4,6,9] and increase antitumor efficacy while reducing systemic toxicity of the anticancer drugs.…”
Section: Emergence and Progress Of Pln Developmentmentioning
confidence: 99%
“…[6] PLN formulations have also been developed to deliver biologics for gene therapy and immunotherapy, including siRNA [7] or siRNA with an anticancer drug. [8] PLN formulations have been shown to circumvent efflux transporter-mediated multidrug resistance (MDR) in cancer cells [1,4,6,9] and increase antitumor efficacy while reducing systemic toxicity of the anticancer drugs. [10,11] It was found that the PLN facilitated drug uptake and retention in P-gp overexpressing cancer cells, provided effective intracellular drug release, transported the drug (e.g.…”
Section: Emergence and Progress Of Pln Developmentmentioning
confidence: 99%
See 2 more Smart Citations